2021
DOI: 10.4314/gm.v21i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ore Grade Estimation Methods for Structurally Controlled Vein Deposits - A Review

Abstract: Resource estimation techniques have upgraded over the past couple of years, thereby improving resource estimates. The classical method of estimation is less used in ore grade estimation than geostatistics (kriging) which proved to provide more accurate estimates by its ability to account for the geology of the deposit and assess error. Geostatistics has therefore been said to be superior over the classical methods of estimation. However, due to the complexity of using geostatistics in resource estimation, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It is also one of the most commonly used methods for the grade estimation of ore bodies. Its calculation formula is 49 , 50 as follows: …”
Section: Methodsmentioning
confidence: 99%
“…It is also one of the most commonly used methods for the grade estimation of ore bodies. Its calculation formula is 49 , 50 as follows: …”
Section: Methodsmentioning
confidence: 99%
“…Recent reviews have shown that neural networks and deep learning models account for ~25% of all ML approaches used in the mining space, with support vector machines (23%) and ensemble methods (22%) close behind [67]. ANNs have been especially useful in mineral resource estimation (e.g., [85][86][87]), comprising ~46% of the ML techniques used in this area [68]. Other prominent applications include mineral prospecting and mapping [88,89], geophysics and remote sensing [90,91], ore classification [92,93], drilling and blasting operations [94,95], mining method selection, equipment utilization and production planning [96,97], ore beneficiation and mineral recovery [98,99] and mine site reclamation [100,101], among others.…”
Section: Appendix B3 Mlp Design Training and Mining Applicationsmentioning
confidence: 99%
“…The attraction of artificial intelligent methods is their flexibility in nature and their ability to capture non-linear relationships between the input and output variables even under the extreme conditions. Through a comparative study of artificial intelligent methods and other methods for ore grade estimation, Abuntori et al (2021) concluded that the AI methods outperformed kriging and other techniques in general. Through a systematic literature review, Mahboob et al (2022) illustrated that the significant AI methods applied for the ore grade estimation are the ANN and SVR.…”
Section: Introductionmentioning
confidence: 99%